Entrepreneurs and consumers perspective on aquaponics and its potential application on tor tambroides and leptobarbus hoevenii in Malaysia - Kiu, Colin Qi Song (2024)
Aquaponics is a sustainable farming method that integrates hydroponics and aquaculture, while aquaponics farming can enhance fish diversity and boost fish production in Malaysian aquaculture. Documenting local entrepreneurs and consumer perspectives has not been done previously, which is pivotal to promote the development and commercialization of aquaponics in Malaysia. Besides, investigating the potential application of aquaponics in culturing Tor tambroides and Leptobarbus hoevenii is also important to improve their productivity within the nation. Two surveys were conducted to investigate the development status of aquaponics operations and consumer perspectives on aquaponics. Additionally, a fish rearing experiment was carried out on two selected high-value native fish species in Malaysia within aquaponics systems. The first survey contains information on the operation and production of 13 commercial aquaponics farms in Malaysia. These aquaponics farms’ most produced crop and fish were leafy vegetables (e.g., lettuce, salad greens, kale, and bak choy) and tilapia, respectively. Aquaponics farmers spent an average of RM 75.44/ft² on the initial capital and RM 16.44/ft² on the annual expenses. On average, the crop value was threefold higher than the fish value produced by these aquaponics farms. Plant pests and diseases, financial issues, pH stabilization, and nutrient deficiencies were the main challenges faced by these farmers. The second survey was conducted to determine consumers’ perceptions and knowledge of aquaponics and its products. Consumers had less experience in practicing aquaponics and purchasing aquaponics products. They had a positive attitude towards the benefits provided by aquaponics and its products but held a neutral attitude towards purchasing and spending more on aquaponics products. A 3 × 2 (fish species × culture system) factorial design experiment was conducted to compare the productivity of empurau (Tor tambroides), jelawat (Leptobarbus hoevenii), and red hybrid tilapia (Oreochromis sp., control) cultured in recirculating aquaculture system (RAS) and aquaponics system. Growth performance, feed conversion ratio, and survival rate of fish were evaluated. The water quality of all tanks was determined throughout the 70-day experiment. Growth performance of empurau and jelawat in weight gain: empurau in aquaponics (390.99%) vs. RAS (390.99%), and jelawat in aquaponics (1111.84%) vs. RAS (1134.89%). For FCR, empurau in aquaponics (2.30) vs. RAS (2.62), and jelawat in aquaponics (1.68) vs. RAS (1.74) were observed in aquaponics as compared to RAS. The result holds the potential to enhance fish production and its diversity, along with promoting aquaponics as a sustainable farming approach to culturing Malaysian indigenous fish species. In summary, aquaponics is still an emerging practice in Malaysia with a promising consumer market. Aquaponics requires more exposure and promotion within the nation to guarantee continuous development in the future of Malaysian aquaculture.